(untitled) (African Disability Rights Yearbook, 2021)
The marginalisation of persons with albinism has for years gone unnoticed. Recently various platforms have been used to combat reported harmful practices against persons with albinism, particularly in Africa. While it is currently accepted that albinism is a human rights agenda, the manner of its advocacy remains unresolved with respect to the ‘appropriate legal approach’ for protecting the rights of persons with albinism. When addressing this problem, two issues appear to be confused: identity (the ‘who are we’ question); and the appropriate legal antidiscrimination approach. Thus, the two issues are distinguished in this contribution by endorsing the ‘appropriate legal anti-discrimination approach’ in realising the rights of persons with albinism. It is worth noting that questions of identity are subjective and should not be confused with objective and empirical questions regarding the appropriate legal mechanisms designed to promote and protect the rights of a particular group. Without downplaying the significance of identity in the formation of the rights groups movement, which has proved vital to the development of human rights, this contribution argues that, while persons with albinism might have multiple identities, the ‘disability rights approach’, which is founded on the social model of disability that uses human rights as a path, is well placed to accommodate matters concerning the rights and equality of persons with albinism.